Effects of lithium on cortical thickness and hippocampal subfield volumes in psychotic bipolar disorder. (February 2015) - Giakoumatos, C.I.; Nanda, P.; Mathew, I.T.; Tandon, N.; Shah, J.; Bishop, J.R.; Clementz, B.A.; Pearlson, G.D.; Sweeney, J.A.; Tamminga, C.A.; Keshavan, M.S.
Abstract: Relative to healthy controls, lithium free bipolar patients exhibit significant gray matter abnormalities. Lithium, the long-time reference standard medication treatment for bipolar disorder, has been proposed to be neuro-protective against these abnormalities. However, its effects on cortical thickness and hippocampal subfield (HSF) volumes remain unstudied and unclear, respectively, in bipolar disorder. This study included 342 healthy controls (HC), 51 lithium free PBD patients (NoLi), and 51 PBD patients taking lithium (Li). Regional gray matter thickness and HSF volume values were extracted from 3T MRI images. After matching NoLi and Li samples, regions where HC differed from either Li or NoLi were identified. In regions of significant or trending HC-NoLi difference, Li-NoLi comparisons were made. No significant HC-Li thickness or HSF volume differences were found. Significantly thinner occipital cortices were observed in NoLi compared to HC. In these regions, Li consistently exhibited non-significant trends for greater cortical thickness relative to NoLi. Significantly less volume was observed in NoLi compared to both HC and Li in right HSFs. Our results suggest that PBD in patients not treated with Li is associated with thinner occipital cortices and reduced HSF volumes compared with HC. Patients treated with Li exhibited significantly larger HSF volumes than NoLi, and those treated with Li were no different from HC in cortical thickness or hippocampal volumes. This evidence directly supports the hypothesis that Li may counteract the locally thinner and smaller gray matter structure found in PBD. Highlights: We test structural impacts of lithium in psychotic bipolar disorder. Lithium free subjects had smaller hippocampi and thinner cortices than controls. No differences were seen between controls and lithium taking subjects. Lithium taking subjects had significantly larger hippocampi than lithium free ones. Lithium may counteract structural abnormalities in psychotic bipolar disorder.